Feasibility analyses of negative-stiffness dampers for seismic performance enhancement of a base-isolated liquid storage tank. Issue 164 (January 2023) - Zhu, H.P.; Tang, Z.A.; Luo, H.
Abstract: Base-isolation systems are widely used to reduce the hydrodynamic base shear and overturning moment of liquid storage tanks with increased isolator displacements and liquid sloshing responses. Supplementing conventional damping devices in the isolation layer can effectively reduce isolator displacements whereas having limited influence on the liquid sloshing. In the present paper, simultaneous reduction on the isolator displacement and sloshing response of a base-isolated liquid storage tank is achieved by using negative-stiffness dampers (NSDs). NSDs consisting of a negative-stiffness component coupled in parallel with a fluid viscous damping component are considered, and an equivalent linearization technique is proposed for designing their properties on the basis of the principle of equal average energy dissipation. A four-lumped-mass model considering high sloshing modes of liquid storage tank is used as a numerical example. The feasibility of NSDs for improving the seismic performance of base-isolated storage tanks with varying aspect ratios is verified. Moreover, nonlinear response history analyses are conducted to illustrate the benefits of the proposed method for the seismic protection of base-isolated storage tanks. The seismic responses of base-isolated storage tanks controlled by using the proposed and traditional methods are comprehensively compared, and it is suggested that the proposed method can be advantageous over conventional ones by more effectively reducing base shear and sloshing responses without compromising isolator displacements. Highlights: A new method is proposed for seismic performance enhancement of base-isolated storage tanks. Simultaneous reduction on isolator displacements and sloshing responses is achieved. An equivalent linearization technique is proposed for designing negative-stiffness dampers. An analytical model considering high sloshing mode of liquid storage tank is developed. Advantages of negative-stiffness dampers over conventional damping devices are identified.